Reconstructing Electoral Law Policy to Strengthen the Prevention and Enforcement of Money Politics in Indonesia - Istiqomah, Milda; Rusli, Hazmi; Agustin, Bunga Veronika Milania; Kurniawan, Heru (Kosmik Hukum, 2026)
Elections constitute a fundamental manifestation of democracy, serving as a crucial mechanism connecting candidates and voters. However, electoral contests continue to be undermined by violations, particularly money politics and political dowries. Article 228 explicitly prohibits the giving and receiving of political dowries in the nomination of presidential and vice-presidential candidates, yet the practice of vote-buying through money or goods persists and has increasingly become embedded as a political culture. This phenomenon threatens democratic integrity, weakens clean governance, and undermines the realization of fair elections. This study examines campaign finance regulation as a preventive legal policy against money politics practices. Employing a normative juridical research method, the study relies on primary and secondary legal materials through a statute approach and a comparative approach. The statute approach is conducted by analyzing the regulatory framework governing campaign finance, criminal provisions, and law enforcement mechanisms related to electoral violations. Meanwhile, the comparative approach is carried out through a micro-level examination of campaign finance limitation policies in the United States in order to construct a preventive model applicable within the Indonesian context. Using deductive legal reasoning and legal syllogism, the research positions legal norms as the major premise and correlates them with relevant legal facts to formulate conclusions. The findings indicate that limiting campaign funds serves as a strategic instrument to reduce excessive monetary influence in politics. Strengthening contribution limits, transparency mechanisms, and law enforcement is therefore essential to prevent money politics and safeguard electoral integrity and democratic accountability.